2016
DOI: 10.1158/1078-0432.ccr-15-2449
|View full text |Cite
|
Sign up to set email alerts
|

Secretome Signature Identifies ADAM17 as Novel Target for Radiosensitization of Non–Small Cell Lung Cancer

Abstract: Purpose: Ionizing radiation (IR) induces intracellular signaling processes as part of a treatment-induced stress response. Here we investigate IR-induced ADAM17 activation and the role of ADAM17-shed factors for radiation resistance in non-small cell lung cancer.Experimental Design: Large-scale secretome profiling was performed using antibody arrays. Secretion kinetics of ADAM17 substrates was determined using ELISA across multiple in vitro and in vivo models of non-small cell lung cancer. Clonogenic survival … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 51 publications
4
48
1
Order By: Relevance
“…Aberrant ADAM17 expression was associated with a poor survival time [39]. ADAM17 can be activated by radiotherapy in NSCLC, which results in shedding of multiple survival factors and growth factor pathway activation [40]. A previous study showed that ADAM17 downregulation suppresses NSCLC migration and invasion [38].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant ADAM17 expression was associated with a poor survival time [39]. ADAM17 can be activated by radiotherapy in NSCLC, which results in shedding of multiple survival factors and growth factor pathway activation [40]. A previous study showed that ADAM17 downregulation suppresses NSCLC migration and invasion [38].…”
Section: Discussionmentioning
confidence: 99%
“…In light of the promising preclinical activity of A17pro in the oncogenic setting of KRAS mutant LAC, we note that previous studies based on the use of non‐specific SMIs (e.g., hydroxamates) or RNA interference‐based approaches (siRNA, shRNA) in NSCLC cell lines have suggested that ADAM17 may have anti‐cancer activity in lung cancer (Zhou et al , ; Baumgart et al , ; Lv et al , ; Sharma et al , ). However, in contrast to our current study, the clinical utility of ADAM17 specifically in mutant KRAS LAC (which accounts for ~15% of all lung cancers) was not investigated.…”
Section: Discussionmentioning
confidence: 95%
“…The limited number of studies investigating ADAM17 in NSCLC has suggested that elevated ADAM17 expression correlates with numerous clinicopathological characteristics (e.g., tumor grade) and poor survival (Ni et al , ). Furthermore , in human NSCLC cell lines, ADAM17 can modulate EGFR signaling either indirectly via Notch1 shedding and activation leading to increased EGFR expression, or directly via shedding of EGFR family ligands, the latter of which may contribute to radiotherapy resistance of NSCLC tumors (Zhou et al , ; Baumgart et al , ; Sharma et al , ). However, the role of ADAM17 in the predominant LAC subtype and its association with KRAS mutation status, as well as the involvement of other ADAM17 substrates in LAC, are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nor did they check whether proteinase activity of ADAM17 is required for the acquisition of IR therapy resistance. Expression of not all ADAM17-cleaved substrates including HB-EGF were increased by irradiation in the paper, and they did not figure out these points (7). Collectively, precise mechanisms of ADAM17-mediated IR therapy resistance still remain to be elucidated by further analysis.…”
mentioning
confidence: 84%
“…Pretreatment with anti-ADAM17 siRNAs or a metalloproteinase inhibitor, TMICommentary Savior or not: ADAM17 inhibitors overcome radiotherapyresistance in non-small cell lung cancer 005 (apratastat), in A549 cells sensitized them to IR and downregulated phosphorylation levels of EGFR. Moreover, a combination of anti-ADAM17 reagents (anti-ADAM17 siRNA or TMI-005) with IR therapy prolonged survival compared with mice taking Cetuximab and IR therapy (7).…”
mentioning
confidence: 99%